Gamma-Irradiated Venezuelan Equine Encephalitis Vaccines - Reitman, Morton (1970)
The efficacy of Formalin-inactivated Venezuelan equine encephalitis (VEE) vaccine has been reported to be low for man. Although a live VEE vaccine has been shown to be highly effective for the protection of laboratory workers, local and systemic reactions have occurred in approximately 20% of inoculated individuals. Therefore, studies were initiated in an attempt to produce an inactivated vaccine of high potency with low toxicity. Inactivated VEE vaccines were prepared by exposing virus suspensions to 8 × 10(6) or 10 × 10(6) r of gamma radiation. Irradiated VEE vaccines prepared from virus suspensions produced in Maitland-type chick embryo (MTCE) cell cultures and in monolayer cultures of human diploid strain WI-38 cells were highly immunogenic for mice and guinea pigs. Guinea pigs vaccinated with a series of three inoculations of vaccine (MTCE) survived challenge with at least 10(8·4) mouse intracerebral 50% lethal doses of VEE virus. Irradiated vaccines induced high levels of serum-neutralizing and hemagglutinin-inhibiting antibodies in guinea pigs and rabbits. These findings suggest that ionizing radiation may be effective in the preparation of an inactivated VEE vaccine.